The JavaScript workshop : a new, interactive approach to learning JavaScript - Labrecque, Joseph; Love, Jahred; Rosenbaum, Daniel; Turner, Nick; Mehla, Gaurav; Hosford, Alonzo L.; Sloot, Florian; Kirkbride, Philip (Packt Publishing, 2019)
Cut through the noise and get real results with a step-by-step approach to beginner JavaScript development.